Navigating English as a Medium of Instruction (EMI) in tertiary education: Challenges, opportunities, and pedagogical strategies for EFL learners - Ahmed, Md Kawser (Ampersand (Oxford, UK), 2025)
The increasing adoption of English as a Medium of Instruction (EMI) in tertiary education has sparked discussions on its potential benefits and challenges for English as a Foreign Language (EFL) learners. This study explores the experiences of EFL learners regarding EMI implementation, focusing on linguistic, academic, and pedagogical dimensions. Employing a qualitative descriptive research design, data were collected through semi-structured surveys from 85 students enrolled in EMI programs. Thematic analysis was conducted using ATLAS.ti to identify key patterns in learner experiences. Findings reveal that while EMI enhances language proficiency, career readiness, and access to academic resources, it also presents significant challenges, including comprehension difficulties, inconsistent teaching methodologies, and reduced classroom participation due to language anxiety. The study underscores the need for gradual EMI implementation, supplementary language support, and faculty training to optimize student learning experiences. The results contribute to the broader discourse on EMI by providing insights into effective pedagogical strategies and policy considerations for higher education institutions. Addressing these challenges through structured adaptation and targeted interventions can enhance EMI effectiveness, ensuring a more inclusive and equitable learning environment for non-native English-speaking students worldwide. English as a Medium of Instruction (EMI): Refers to the use of English for teaching academic subjects in non-native English-speaking regions.F0B7Challenges of EMI:•Language proficiency issues among students and teachers.•Misalignment of curriculum objectives with language capabilities.•Inequalities in access to resources and training.F0B7Benefits of EMI:•Enhances global competitiveness and career prospects.•Facilitates international collaboration and mobility.F0B7Impact on Education:•Influence on student learning outcomes and classroom interaction.•Pressure on educators to balance content delivery with language instruction.F0B7Policy and Implementation:•Need for tailored strategies and teacher training programs.•Importance of context-sensitive approaches to EMI adoption.